Continuous education in the Family Health Program: a qualitative study - Zavarese da Costa, Valdecir; Cezar-Vaz, Marta Regina; Silveira Cardoso, Leticia; de Souza Soares, Jorgana Fernanda (Investigación y Educación en Enfermería, 2010)
<!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> Objective. To analyze the continuous education in the work process spectrum of the Family’s Health Program in Brazil, through its performers, performing place, way of development and goal. Methodology. Qualitative study in which a semi structured interview was performed to 65 nurses. Results. Educational activities are conceived by the interviewed nurses as an action which goal is the work process qualification: either helping the nurse in his job or helping in the building of a propulsive health actions strength in several stages of action. Conclusion. With continuous education both the nurse and their work environment are qualified.